Effect of Facility Ownership on Utilization of Arthroscopic Shoulder Surgery. Issue 5 (1st March 2018) - Black, Eric M.; Reynolds, John; Maltenfort, Mitchell G.; Williams, Gerald R.; Abboud, Joseph A.; Lazarus, Mark D.
Abstract : Introduction: We examined practice patterns and surgical indications in the management of common shoulder procedures by surgeons practicing at physician-owned facilities. Methods: This study was a retrospective analysis of 501 patients who underwent arthroscopic shoulder procedures performed by five surgeons in our practice at one of five facilities during an 18-month period. Two of the facilities were physician-owned, and three of the five surgeons were shareholders. Demographics, insurance status, symptom duration, time from injury/symptom onset to the decision to perform surgery (at which time surgical consent is obtained), and time to schedule surgery were studied to determine the influence of facility type and physician shareholder status. Results: Median duration of symptoms before surgery was significantly shorter in workers' compensation patients than in non–workers' compensation patients (47% less; P < 0.0001) and in men than in women (31% less; P < 0.001), but was not influenced by shareholder status or facility ownership ( P > 0.05). Time between presentation and surgical consent was not influenced by facility ownership ( P = 0.39) or shareholder status ( P = 0.50). Time from consent to procedure was 13% faster in physician-owned facilities than in non–physician-owned facilities ( P = 0.03) and 35% slower with shareholder physicians than with nonshareholder physicians ( P < 0.0001). Discussion: The role of physician investment in private healthcare facilities has caused considerable debate in the orthopaedic surgery field. To our knowledge, this study is the first to examine the effects of shareholder status and facility ownership on surgeons' practice patterns, surgical timing, and measures of nonsurgical treatment before shoulder surgery. Conclusions: Neither shareholder status nor facility ownership characteristics influenced the speed with which surgeons determined that shoulder surgery was indicated or surgeons' use of preoperative nonsurgical treatment. After the need for surgery was determined, patients underwent surgery sooner at physician-owned facilities than at non–physician-owned facilities and with nonshareholder physicians than with shareholder physicians. Level of evidence: Level III